Comparison of Burrowing and Stimuli-Evoked Pain Behaviors as End-Points in Rat Models of Inflammatory Pain and Peripheral Neuropathic Pain - Muralidharan, Arjun; Kuo, Andy; Jacob, Meera; Lourdesamy, Jacintha S.; Carvalho, Lara Melo Soares Pinho De; Nicholson, Janet R.; Corradini, Laura; Smith, Maree T. (Frontiers in Behavioral Neuroscience, 2016)
Establishment and validation of ethologically-relevant, non-evoked behavioral end-points as surrogate measures of spontaneous pain in rodent pain models has been proposed as a means to improve preclinical to clinical research translation in the pain field. Here, we compared the utility of burrowing behavior with hypersensitivity to applied mechanical stimuli for pain assessment in rat models of chronic inflammatory and peripheral neuropathic pain. Briefly, groups of male Sprague-Dawley rats were habituated to the burrowing environment and trained over a 5-day period. Rats that burrowed ≤450g of gravel on any two days of the individual training phase were excluded from the study. The remaining rats received either a unilateral intraplantar injection of Freund’s complete adjuvant (FCA) or saline, or underwent unilateral chronic constriction injury (CCI) of the sciatic nerve- or sham-surgery. Baseline burrowing behavior and evoked pain behaviors were assessed prior to model induction, and twice-weekly until study completion on day 14. For FCA- and CCI-rats, but not the corresponding groups of sham-rats, evoked mechanical hypersensitivity developed in a temporal manner in the ipsilateral hindpaws. Although burrowing behavior also decreased in a temporal manner for both FCA- and CCI-rats, there was considerable inter-animal variability. By contrast, mechanical hyperalgesia and mechanical allodynia in the ipsilateral hindpaws of FCA- and CCI-rats respectively, exhibited minimal inter-animal variability. Our data collectively show that burrowing behavior is altered in rodent models of chronic inflammatory pain and peripheral neuropathic pain. However, large group sizes are needed to ensure studies are adequately powered due to considerable inter-animal variability.